TI_GERICHTE 17.2016.216 vom 28. März 2017 , Superamento limite di velocitâ di 44 km/h su tratto limitato a 100 km/h - TI Tribunale d'appello (2017)
Superamento limite di velocitâ di 44 km/h su tratto limitato a 100 km/h